Importance of cultivars x locations and cultivars x years interactions in maize evaluation in the "safrinha" - Gonçalves, Flávia Maria Avelar; Carvalho, Samuel Pereira de; Ramalho, Magno Antonio Patto; Corrêa, Luiz André (Pesquisa Agropecuaria Brasileira, 1999)
Aiming to check the importance of cultivars x locations and cultivars x years interactions, and to identify among the available hybrids those which are most adapted and stable for cultivation in "safrinha", the parameters of adaptability and stability were studied using the data previously obtained in some evaluation trials of maize cultivars in the "safrinha" during the years of 1993, 1994 and 1995. The experiments were conducted in the states of São Paulo, Goiás and Paraná, in Brazil. The experimental design utilized was in randomized blocks with 3 replications. It was verified that the magnitude of variation of the interactions of the cultivars x years inside the localities was more prominent than that by localities, indicating the necessity that evaluations of the cultivars in the harvesting period be accomplished in more years. The cultivars differed based on adaptability and stability of grain yield. The materials that distinguished themselves as more adaptable and stable were the simple hybrid Zeneca 8452, the triple hybrid C 805 and the double hybrid Agromen 2012. Now, the double hybrids BR 201, Planagri 411, AG 303 and C 125 were those that showed lesser adaptability and higher instability.